KENDALI LAMPU RUMAH VIA SMS BERBASIS MIKROKONTROLER ATMEGA32L - Nurul Zainal Fanani; Puspa Grahito Adhi (Jurnal Teknologi Informasi dan Terapan, 2019)
In today's technological era in the development of all areas with extremely rapid technological base. Various inventions and technological developments have made a lot of changes for a wide range of growing order of life in the community. This helps facilitate human progress in completing the work that had been considered difficult and almost impossible to do. One of them is the field control with the discovery of the microcontroller as a tool automatic control. Through this thesis the author will use the microcontroller ATMega32L as one of the few products to control the light output ATMEL home via SMS with the method on / off controller. The author uses the C programming language as programming for microcontroller ATMega32L. Control lights via sms is designed to turn on and turn off the lights with command via SMS. From the test results as a whole it can be concluded that the system can work well, it is seen from the results of testing that includes testing process.